A content analysis of Cambridge general certificate of education examination papers ordinary level in Mathematics 1960-1969 - Leong, Swee-Gin 1943- (s.n.], 1970)
This research paper seeks to analyze the content of the mathematics papers (Alternative B) of the Cambridge School Certificate Examination with regards to the subject classification and emphasis of the questions, the readability of the questions, the time allocation and mark distribution of the questions, and the classification of mathematical abilities required in the questions. Alternative B was chosen because most students in Malaysia and Singapore take it as one of their subjects. The research used content analysis and classified the 220 examination questions according to subjects: Arithmetic, Algebra, Trigonometry, Geometry, and Applied Geometry. Based from the findings, the most basic and frequently called-for mathematical abilities were determined.